Parodi Politik dalam Demokrasi Digital Studi Kasus: Akun Instagram Nurhadi-Aldo - Bhakti Satrio Wicaksono (PERSPEKTIF, 2021)
This article aims to find out what happened to digital democracy regarding the Dildo account case. This research uses descriptive qualitative research research methods. The type of observation method used is the non-participation observation method. The non-participant observation method is the method that researchers chose in conducting this research. The results of the study show that the view of digital democracy can be seen from two perspectives, namely the government and the people's point of view. Political parody basically offers a new way of engaging in the political world. The Dildo case shows that not everyone can freely express their opinion on social media. The freedom to voice opinions, especially through cyberspace, still cannot be said to be free. This can be seen with how when the Dildo account voices humor and national issues that are close to the public, it still gets contra opinions from other parties. The conclusion of the research is that political parody basically offers a new way of engaging in the political world. Dildo case shows that not everyone can freely express their opinion in social media. The existence of internet technology in terms of statehood can be a double-edged knife, especially on social media where information is spread so fast. Parody or current humor is treated wisely and is not necessarily considered a dangerous thing.